Commons Praxis: Toward a Critical Political Economy of the Digital Commons - Benjamin J Birkinbine (tripleC: Communication, Capitalism & Critique)
The concept of the commons has provided a useful framework for understanding a wide range of resources and cultural activities associated with the creation of value outside of the traditional market mechanisms under capitalism (i.e., private property, rational self-interest, and profit maximization).  However, these communities often continue to intersect with capital and the state attempts to appropriate their resources. Recent scholarship has sought to unpack some of the contradictions inherent in the claims made about the revolutionary potential of the commons by offering conceptual frameworks for assessing commons-based projects.  This paper builds upon this research by developing a two-pronged argument.  First, by drawing examples from the free software movement, I argue that critical political economy provides the most useful analytical framework for understanding the contradictions inherent in the relationship between capital and the commons. Second, I argue for a commons praxis that attempts to overcome some of these contradictions.  Within this discussion, I build on the notion of ‘boundary commoning’ to understand organisational form, and I develop the concept of ‘subversive commoning’ for understanding various forms of commoning that seek to undermine the capitalist logics of the digital commons.